DESKRIPSI KONSEPTUAL TENTANG INTERNALISASI NILAI IMAN DAN AKHLAK DALAM PEMBELAJARAN PAI BERBASIS PROYEK - kurniawan, muhammad mauludi (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2025)
Islamic Religious Education (PAI) plays a crucial role in shaping students’ faith, morality, and Islamic character in daily life. In the context of rapid technological advancement and social change, Islamic education must shift from a cognitive-oriented approach to one emphasizing experiential and reflective learning. This study explores how Project-Based Learning (PjBL) serves as an effective strategy for internalizing values of faith (iman) and morality (akhlak). Using a qualitative descriptive approach through literature review, this research highlights the relevance of PjBL in connecting Islamic teachings with students’ social and spiritual practices. The findings indicate that PjBL fosters active engagement, moral responsibility, and religious collaboration among learners. The internalization of iman and akhlak occurs through structured reflection, teacher exemplification, and contextual projects that nurture spiritual awareness and ethical behavior. However, its effectiveness depends on clear assessment rubrics, teacher training, and institutional support. The study concludes that PjBL is a pedagogical approach with strong potential to enhance the affective dimension of Islamic education and promote the development of students’ religious character.